PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SD NEGERI 49 TAMERAN KECAMATAN BENGKALIS - Sumiyati, Sumiyati; Noviana, Eddy; Syahrilfuddin, Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack : The backgraund of the problem this research is the low of natural science learning results of students. Can be seen from 20 students only 8 students who achieve KKM (40%) and 12 students did not reach KKM (60%) with the average value of 65,75, classical completeness is said to be complete if reached 85%. For the result to learn science be increased, researchers chose to cooperative learning model Make A Match. Teacher activity on cycle 1 first meeting 62, 5% with both categories, while on the second meeting increased to 66,6% with both categories. Then on cycle of 2 first meeting 75,0% with both categories, while on the second meeting increased to 91,6% with very good category. While the activity of students on cycle 1 the first meeting 58,3% with enough category, while on the second meeting increased to 62,5% with both categories, Then on cycle of 2 first meeting 70,8% with both categories, while the second meeting increased to 87,5% with very good category. On the daily tests 1 showed an average increase of the basic score 65,75 into 68,75 with an increase of 4,56%, then on the daily test 2 average increased to 76,75 with an increase of 16,73%. So conclusion is the implementation of cooperative learning model Make A Match on natural science learning can improve student learning results of class III SD Negeri 49 Tameran Kabupaten Bengkalis.Keywork: Coperative Learning Model Make A Match, IPA Learning Result